Pentingnya Pembelajaran Sor Singgih Bahasa Bali Sebagai Budaya Bali Bagi Siswa SD - Ketut Susiani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
The Balinese language is historical evidence for Balinese people who are domiciled as a vehicle for Balinese cultural expression, in which aesthetic, religious, social, political, and other aspects of Balinese life are recorded. The Balinese language is one of the regional languages that has a multi-level language system (anggah-ungguhing basa/sor singgih basa Bali). The purpose of this study was to provide elementary school students with an understanding of the importance of learning the Balinese language asSor Singgih as Balinese culture. The method used in this study is a qualitative method with interview and observation techniques. The results of this research are that it is important for us to teachSor Singgih Balinese language to students, in addition to communicating with other people, we can also introduce the culture of the Balinese language to others. this can be done by using a short storybook, sample stories can make it easier for students to understandSor Singgih Balinese language.